Designing a Workplace Health Model for Creative Industry Employees in Tourism Villages: A Grounded Theory Approach” - Riana, Meisi; Latif, Antinah; Annishia, Fristi Bellia; Elviana, Elviana; Shabir, Fadly (Politeknik Negeri Bengkalis, 2024)
Tourism villages are one of the fastest growing sectors in the creative industry. Healthy workplace conditionsare essential to support employees in generating innovation and creativity. However, workplace health in this sector isoften neglected. This research aims to design a workplace wellness model suitable for creative industry employees intourist villages, using a Grounded Theory approach. The method involved in-depth interviews with 20 employees and 2managers from a pilot tourist village. Data were analyzed through open, axial, and selective coding stages to identifyfactors affecting occupational health. The results revealed that lack of government regulation and supervision, high workpressure, and lack of health facilities are some of the main challenges faced by employees. In addition, low managerialsupport for employee health also worsened workplace conditions. Based on these findings, the proposed workplacehealth model is the socialization and education of existing OSH regulations, establishing partnerships with OSHinstitutions or external parties, managing work stress, and providing better health facilities. This model is expected toimprove the physical and mental well-being of employees, while encouraging productivity and work quality in thecreative industry sector of tourist villages. The main suggestion from this research is the importance of more attentionfrom the management of tourist villages in implementing a comprehensive occupational health policy to create a healthierwork environment and support innovation.